2003
DOI: 10.1038/sj.hdy.6800336
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of resistance to mercury poisoning in steelhead (Oncorhynchus mykiss) alevins

Abstract: Newly hatched steelhead alevins were obtained from the factorial breeding of 24 male and 10 female steelhead trout, Oncorhynchus mykiss. Each set of offspring were in a separate cell. They were tested for resistance to intoxication by methylmercuric chloride (CH 3 HgCl) in water at a nearly constant mercury concentration of 8 mg l À1 . High mortality (81% of the tested alevins) occurred within 2 weeks. Resistance to intoxication, as measured by the time to death, as well as by the survival rate, shared high pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Mercury tolerance has been evaluated in few vertebrates. To our knowledge it has only been described in fish [ 37 , 38 ] and in a previous study where we demonstrated reproductive differences among families of zebra finches exposed to mercury [ 22 ]. We are not aware of any published studies of the heritability of traits related to mercury accumulation or tolerance in a terrestrial vertebrate species.…”
Section: Introductionmentioning
confidence: 79%
“…Mercury tolerance has been evaluated in few vertebrates. To our knowledge it has only been described in fish [ 37 , 38 ] and in a previous study where we demonstrated reproductive differences among families of zebra finches exposed to mercury [ 22 ]. We are not aware of any published studies of the heritability of traits related to mercury accumulation or tolerance in a terrestrial vertebrate species.…”
Section: Introductionmentioning
confidence: 79%
“…Thus, there is empirical evidence that pollutants may act as one of the selective forces in the environment and that genetic adaptation to pollutants is both possible and can occur naturally. Empirical results from family based experiments also show that accumulation of mercury in the body is highly heritable in steelheads (Blanc et al, 2003 ) and zebra finches (Buck et al, 2016 ). The fact that a strong genetic component is observed in such disparate taxa strengthens the assumption that genetic differences generally affect mercury accumulations in vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68][69][70] Importantly, maternal effects have been shown to account for variation in performance, stress resistance, and life history traits in cases where the embryo heavily relies on large maternally produced yolk and albumen reserves for growth and development. [71][72][73][74] Synthesis of these studies strongly suggested that maternal effects during early development can have a long-lasting impact on the adult phenotype by changing developmental trajectories, as well as having an acute impact on embryonic development and function.…”
Section: Transgenerational Epigenetics In Ecology and Physiologymentioning
confidence: 97%